1973
DOI: 10.1128/jb.116.3.1191-1198.1973
|View full text |Cite
|
Sign up to set email alerts
|

Role of Methionine in Biosynthesis of Prodigiosin bySerratia marcescens

Abstract: Methionine alone did not allow biosynthesis of prodigiosin (2-methyl-3amyl-6-methoxyprodigiosene) in nonproliferating cells (NPC) of Serratia marcescens strain Nima. However, when methionine was added to NPC synthesizing prodigiosin in the presence of other amino acids, the lag period for synthesis of prodigiosin was shortened, an increased amount of the pigment was formed, and the optimal concentrations of the other amino acids were reduced. Less prodigiosin was synthesized when addition of methionine was del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…We previously analyzed ( Kurbanoglu and Kurbanoglu, 2004 ) the chemical composition of RHP and determined that it is very rich in both organic and inorganic nutrients and contains many amino acids and inorganic materials (data are not given). Others have reported that some amino acids (alanine, serine, histidine, cystine, methionine, glutamate, tryptophan and proline) contribute to the formation of prodigiosin ( Williams et al , 1971 ; Qadri and Williams, 1973 ; Witney et al , 1977 ). The results of our previous studies ( Kurbanoglu and Kurbanoglu, 2004 ; Kurbanoglu 2004b ; Kurbanoglu and Kurbanoglu, 2007 ) showed that RHP contains all of these amino acids at varying concentrations and is especially rich in alanine, cysteine, glutamate and proline.…”
Section: Resultsmentioning
confidence: 99%
“…We previously analyzed ( Kurbanoglu and Kurbanoglu, 2004 ) the chemical composition of RHP and determined that it is very rich in both organic and inorganic nutrients and contains many amino acids and inorganic materials (data are not given). Others have reported that some amino acids (alanine, serine, histidine, cystine, methionine, glutamate, tryptophan and proline) contribute to the formation of prodigiosin ( Williams et al , 1971 ; Qadri and Williams, 1973 ; Witney et al , 1977 ). The results of our previous studies ( Kurbanoglu and Kurbanoglu, 2004 ; Kurbanoglu 2004b ; Kurbanoglu and Kurbanoglu, 2007 ) showed that RHP contains all of these amino acids at varying concentrations and is especially rich in alanine, cysteine, glutamate and proline.…”
Section: Resultsmentioning
confidence: 99%
“…Such a study was made possible by addition of proline to non-proliferating suspensions of strain Nima, the Aut mutant, and the Hut mutant, and of alanine to nonproliferating suspensions of the Put mutant, to induce metabolism and pigmentation ( Table 5). L-Methionine was added to these suspensions to increase the quantity of pigment formed (9). Once pigment was formed, labeled alanine, histidine, or proline was added to the cell suspensions, and the incorporation of these amino acids into the pigment was followed.…”
Section: Resultsmentioning
confidence: 99%
“…After 12 h of incubation, radioactive proline was added to the cell suspension. At 16 h of incubation, prodigiosin was extracted from the cells, purified, and counted for radioactivity (12).…”
Section: Resultsmentioning
confidence: 99%